2007
DOI: 10.1021/ac060527f
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Rule-Building Expert System Classification of Fuel Using Solid-Phase Microextraction Two-Way Gas Chromatography Differential Mobility Spectrometric Data

Abstract: Gas chromatography/differential mobility spectrometry (GC/DMS) has been investigated for characterization of fuels. Neat fuel samples were sampled using solid-phase microextraction (SPME) and analyzed using a micromachined differential mobility spectrometer with a photoionization source interfaced to a gas chromatograph. The coupling of DMS to GC offers an additional order of information in that two-way data are obtained with respect to compensation voltages and retention time. A fuzzy rule-building expert sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…In this paper, an expert system approach is chosen because of its maturity and because it has been used successfully at solving other problems (Holzmann et al, 1999;Rearden et al, 2007;Wentz et al, 2008). …”
Section: Concept Of the Classificationmentioning
confidence: 99%
“…In this paper, an expert system approach is chosen because of its maturity and because it has been used successfully at solving other problems (Holzmann et al, 1999;Rearden et al, 2007;Wentz et al, 2008). …”
Section: Concept Of the Classificationmentioning
confidence: 99%
“…Two-dimensional GC was used in conjunction with PCA to classify samples of jet fuel [305]. Samples of diesel fuel and jet fuel were classified using a differential mobility spectrometer (DMS) with a photoionization source interfaced to a gas chromatograph [306]. Principal component analysis was used to distinguish between samples of evaporated kerosene and diesel fuel [307].…”
Section: Chemical Fingerprintingmentioning
confidence: 99%
“…But generally in these data sets, we seek to determine relatively simple information from the data stream. Occasionally, we also may be interested in detecting groups of several chemicals from a complex mixtures, but still only identifying a handful of major chemical features which is a small finite number (Camara et al 2013; Lu and Harrington 2007; Rearden et al 2007). In some examples, signal alignment has been used (Krebs et al 2006a), along with feature selection procedures (Fong et al 2011; Zhao et al 2009) to assist in chemical identification.…”
Section: Introductionmentioning
confidence: 99%
“…Frequently these local optima are not general enough to be applied to data not used in training the model. A fuzzy rule building expert system (Rearden et al 2007) has also been demonstrated for synthetic complex mixtures, such as JP-8 jet fuel, and may also be appropriate for metabolomic data sets. Linear discriminant analysis (Covington et al 2013; Rutolo et al 2014) and Fisher discriminant analysis (Arasaradnam et al 2014b) have been used as classification methods for biological data as well.…”
Section: Introductionmentioning
confidence: 99%